Does additive pressurized carbon dioxide lavage improve cement penetration and bond strength in cemented arthroplasty? - Knappe, Kevin; Stadler, Christian; Innmann, Moritz Maximilian; Schonhoff, Mareike; Gotterbarm, Tobias; Renkawitz, Tobias; Jäger, Sebastian (Journal of Clinical Medicine, 2021)
The modern cementing technique in cemented arthroplasty is a highly standardized and, therefore, safe procedure. Nevertheless, aseptic loosening is still the main reason for revision after cemented total knee or cemented total hip arthroplasty. To investigate whether an additional carbon dioxide lavage after a high-pressure pulsatile saline lavage has a positive effect on the bone-cement interface or cement penetration, we set up a standardized laboratory experiment with 28 human femoral heads. After a standardized cleaning procedure, the test implants were cemented onto the cancellous bone. Subsequently, the maximum failure load of the bone-cement interface was determined using a material testing machine to pull off the implant, and the cement penetration was determined using computed tomography. Neither the maximum failure load nor cement penetration into the cancellous bone revealed significant differences between the groups. In conclusion, according to our experiments, the additive use of the carbon dioxide lavage after the high-pressure pulsatile lavage has no additional benefit for the cleaning of the cancellous bone and, therefore, cannot be recommended without restrictions.